ISLAM PROGRESIF, MARXISME, DAN TAN MALAKA - Tohis, Reza Adeputra (Jurnal JINNSA (Jurnal Interdipliner Sosiologi Agama), 2023)
This article examines the relationship between progressive Islam, Marxism, and Tan Malaka. Progressive Islam is one of the new movements in contemporary Islamic dynamics. Marxism is a tradition of thought. Tan Malaka is one of the Muslim leaders who uses the tradition of Marxism in every thought and struggle. This article uses the method of philosophy with the technique of historical-factual study of figures. Data analysis uses the concept of externalization from the sociological theory of knowledge. The result is that Marxism is one of the external spaces of progressive Islam, where its characters externalize. Similarly to progressive Islamic figures, Tan Malaka also externalized Marxism, so that he could have knowledge about Marxism. Thus Marxism became the connecting bridge between progressive Islam and Tan Malaka. This is the relationship between progressive Islam, Marxism, and Tan Malaka.